(untitled) (Research, Society and Development, 2021)
The present study aimed to assess the relationship between dietary vitamin C intake and activity of antioxidant enzymes in obese women. This is a case-control study, involving 62 women, aged between 20 and 50 years, divided into two groups: control group (eutrophic women, n = 40) and case group (obese women, n = 22). The measures of weight and height were considered to calculate the body mass index, as well as the estimated intake of calories, macronutrients and vitamin C. In addition, blood samples were collected from the participants for further analysis of the erythrocyte activity of the enzymes glutathione peroxidase and superoxide dismutase. The data were analyzed using the statistical program SPSS for Windows 22.0. As for the results, a statistically significant difference was observed regarding the consumption of carbohydrates and lipids (p <0.05), being lower in the case group. Moreover, obese women ingested less vitamin C than the control group (p <0.05). The activity of the glutathione peroxidase enzyme was similar in the groups, however, reduced activity of the superoxide dismutase enzyme was observed in obese women (p <0.05). There was no correlation between the parameters of vitamin C and antioxidant enzymes in the groups. Wherefore, it is concluded that the intake of vitamin C did not seem to influence the activity of antioxidant enzymes.